Applying microdroplets as sensors for label-free detection of chemical reactions - Hofmann, Tobias; Hänselmann, Siegfried; Janiesch, Jan-Willi; Rademacher, Anne; Böhm, Christian H. J. (Lab on a chip, 2012)
Despite its tremendous high-throughput screening capabilities, widespread applications of droplet-based microfluidics are still limited by the poor availability of appropriate analytical assays. Here we report on a novel sensor method that exploits the osmosis-driven change in droplet size as a quantitative and label-free marker for reactions inside the droplets. We present an analysis of the underlying mechanism and apply the method for monitoring metabolic activity at a single-cell level.